Specialization for aggression in sexually dimorphic skeletal morphology in grey wolves (Canis lupus) - Morris, Jeremy S (Blackwell Science Inc, 2014)
Aggressive behaviour is important in the life history of many animals. In grey wolves (Canis lupus), territory defence through direct competition with conspecifics is severe and often lethal. Thus, performance in aggressive encounters may be under strong selection. Additionally, grey wolves frequently kill large dangerous prey species. Because both sexes actively participate in aggressive activities and prey capture, wolves are expected to exhibit a low level of musculoskeletal sexual dimorphism. However, male wolves more often lead in agonistic encounters with conspecifics and must provision the nursing female during the pup-rearing period of the breeding season. These behaviours may select for males that exhibit a higher degree of morphological adaptation associated with aggression and prey capture performance. To test this prediction, we assessed skeletal sexual dimorphism in three subspecies of grey wolves using functional indices reflecting morphological specialization for aggression. As expected, sexual dimorphism in skeletal shape was limited. However, in two of three subspecies, we found sexually dimorphic traits in the skull, forelimbs and hindlimbs that are consistent with the hypothesis that males are more specialized for aggression. These characters may also be associated with selection for improved prey capture performance by males. Thus, the sexually dimorphic functional traits identified by our analysis may be adaptive in the contexts of both natural and sexual selection. Several of these traits may conflict with locomotor economy, indicating the importance of aggression in the life history of male grey wolves. The presence of functional specialization for aggression in a generally monogamous species indicates that sexual dimorphism in specific musculoskeletal traits may be widespread among mammals.